Transformative service research at the BoP: the case of Etawa goat farmers in Indonesia. Issue 5 (18th April 2020) - Dean, Alison; Indrianti, Nur
Abstract : Purpose: The purpose of this study is to explore how value creation and transformative service research (TSR) are interconnected at the base of the pyramid (BoP). To do so, the study seeks consumers' perceptions of changes in well-being from value creation and the means by which these changes become transformative. Design/methodology/approach: A qualitative, longitudinal design was used, involving a community education project in Indonesia. Data collection consisted of interviews with Etawa goat farmers and village leaders after one year ( n = 21), and a further three years ( n = 10). Findings: Findings from the study are used to advance a model for value creation and TSR at the BoP, which identifies three critical change periods within consumers. These periods suggest that creating improvements in well-being of consumers requires their initial recognition of value outcomes, realisation of agency and a new vision for the future. Research limitations/implications: Research in other contexts is warranted to confirm the model, to further explore well-being from service at the BoP and to identify issues that diminish consumers' confidence and stall transformation. Methodological challenges at the BoP also present avenues for insightful work. Practical implications: Transformative service at BoP requires an emphasis on suitable structures, collaborative processes and management skills to facilitate consumers gaining agency and control, so that they can use their new and existing resources effectively and/or differently. Social implications: Participants highlighted positive changes to well-being at both individual and collective levels. Notably, some changes were not directly related to initial service provision but reflected improvements, such as employment for women, and better hygiene, health and education of families. Originality/value: By exploring the interconnection between transformative service and value creation, this study addresses the issue of when value creation becomes transformative and vital for poverty alleviation at the BoP. The proposed model incorporates TSR, service logic and other literature, illustrates a process moving from value determination to value expansion and highlights three critical intrasubjective change periods within actors.